Kuroneko Based on a Japanese Folktale - Shindo, Kaneto; Igawa, Norimichi; Kuroda, Kiyomi; Satô, Kei; Nakamura, Kichiemon; Otowa, Nobuko (Eureka Video, 2009)
Loosely based on a Japanese folktale entitled "The Cat's Revenge", "Kuroneko" is a spare, atmospheric, sensual, and acutely haunting portrait of love, duty, revenge, and inhumanity. Kaneto Shindo juxtaposes elemental and poetic natural imagery with the abstract, highly stylized expressionism of Noh theater to create an indelible aesthetic of visual dichotomy that exposes the underlying contradiction and hypocrisy of tolerated societal behavior. From the introductory presentation of the disheveled, unnamed rogue army leader who participates in the terrorization of the women, then subsequently re-emerges as a distinguished samurai who, nevertheless, is eager to exploit an opportunity to pursue a captivating and seemingly vulnerable young woman walking home alone, Shindo examines similar themes of innate primitivism, godlessness, and violence that exist beneath the veneer of civility as his earlier feature, "Onibaba". [www.filmref.com]
Keywords: DVD-Video